Common imitators of epilepsy. (29th November 2012) - Brodtkorb, E.
Abstract : Many episodic phenomena involving motor, sensory, autonomic, and behavioral functions may imitate epilepsy. The aim of this article is to focus on the various manifestations and the diagnostic and therapeutic challenges of the most common of these disorders, as well as their relationship to emotional aspects. Syncope is caused by reduced global cerebral perfusion. Convulsive movements are sometimes released from subcortical structures, but do not follow the characteristic sequence of tonic–clonic seizures, and postictal symptoms are minimal. Hyperventilation attacks are caused by the metabolic consequences of hypocapnia. Altered blood pH and cerebral vasoconstriction may cause a range of peripheral and central nervous system symptoms. Psychogenic non‐epileptic seizures (PNES) are attacks of reduced self‐control associated with various behavioral phenomena, usually beyond voluntary control. A detailed clinical history is the most important tool in the differential diagnosis. Various emotional factors may act as immediate triggers in reflex syncope and hyperventilation attacks, whereas in PNES, emotional traumas may be remote and suppressed. Patient education with appropriate explanation of the underlying mechanisms is a fundamental part of the management of these disorders.